The efficacy of botulinum toxin type A treatment and surgery for acute acquired comitant esotropia - Li, Yipao; Tong, Luyao; Chen, Yuanyuan; Zhang, BinJun; Wan, Minghui; Yin, Xiangping; Zhang, Fang (Frontiers in Medicine, 2023)
Aim To compare the long-term efficiency of botulinum toxin type A (BTXA) injection and surgery on acute acquired comitant esotropia (AACE). Methods This retrospective study enrolled patients with AACE from January 2020 to August 2022. The horizontal angle of deviation pre- and post-treatment was measured. Deviations in BTXA and surgical treatment were compared. The BTXA group was divided into adequate treatment (AT) and inadequate treatment (inAT) subgroup based on the deviation of no more than 4 prism diopters (at near and distance) or temporary exotropia at the 2 week follow-up. The two subgroups were compared to determine the long-term efficacy of BTXA treatment. Results Ninety-two patients with AACE were included. Follow-up was 6 months. The deviations of the surgery and BTXA group were significantly smaller at the 6 month follow-up than at pre-treatment (p < 0.001). The deviation before treatment in the surgery group was larger than in the BTXA groups (p < 0.001) but smaller at the 6 month follow-up (p < 0.001). The deviation was similar in the AT-BTXA and inAT-BTXA subgroups before treatment (p = 0.322 for distance and p = 0.051 for near) but smaller in the AT-BTXA subgroup at 6 month follow-up (p < 0.001 for near and distance). Conclusion Surgery and BTXA successfully treat AACE. Surgery has a more precise and lasting therapeutic effect than BTXA. AACE patients adequately treated with BTXA and with deviations of no more than 4 prism diopters at 2 weeks follow-up had better outcomes.